GAMBARAN KADAR SERUM GLUTAMATE OXALOCETIC TRANSMINASE (SGOT) DAN GLUTAMATE PYRUVAT TRANSMINASE (SGPT) PADA PASIEN DIABETES MELITUS DI RSUD SYEKH YUSUF KAB.GOWA - Suharsih Thahir; Asni Hasanuddin; Dian Hardianti (Jurnal Media Laboran, 2019)
This study is based on the high levels of SGOT and SGPT in Diabetes Mellitus patients. Indonesia is the country with the 4th largest number of people with diabetes mellitus in the world after China, India, and the United States. Every year there are 3.2 million deaths caused directly by Diabetes Mellitus. This study is a laboratory experimental research which is dexritive. Samples in this study were taken by means of purposive sampling as many as 20 blood samples in RSUD Syekh Yusuf Kab. Gowa examined at the Laboratory of Syekh Yusuf District Hospital. Gowa The results of studies conducted on 20 blood samples of Diabetes Mellitus patients obtained 5 (25%) elevated SGOT and SGPT levels and, 15 (75%) normal SGOT and SGPT levels. It is recommended for sufferers to avoid or pay attention to their physical health or complications caused by Diabetes Mellitus. It is necessary to hold extensive public health education, and increase awareness about healthy eating patterns and exercise for a healthier way of life.